Allocation and Ex Ante Cost Efficiency of a Swedish Subsidy for Environmental Sustainability: The Local Investment Program - Maria Vredin Johansson (Uppsala University, Department of Economics, 2004)
We evaluate the allocation rationality and ex ante cost efficiency of a major Swedish investment subsidy program, the Local Investment Program (LIP). The LIP, effective between 1998-2002, had dual purposes: to step up the pace at which Sweden transforms into an ecologically sustainable society and to reduce unemployment. During the program period, more than 6.2 billion Swedish kronor (approximately Euro 670 million) were granted to different municipal projects. By using data on the projects subsidies and anticipated environmental and employment effects, we find that these effects to a high degree explain the magnitude of the subsidy granted. We find that the marginal LIP subsidy for carbon dioxide (CO2) reductions does not vary significantly over the projects, implying that the LIP was cost efficient for such reductions. Furthermore, for a majority of the projects, the marginal subsidy for CO2 reductions was lower than the, at the time, prevailing CO2 tax. Assuming successful project fulfillment, we conclude that the LIP was a low cost, cost efficient environmental policy for reducing CO2 emissions provided that the projects generate spillover effects large enough to justify the subsidy.
urn:nbn:se:uu:diva-4515
Keywords: Q56; Q58; 330; Environmental policy; evaluation; greenhouse gas; spillover effect; subsidy; Umweltpolitik; Umweltschutzinvestition; Kosten-Wirksamkeits-Analyse; Schweden